Design, Synthesis, and Characterization of New 1,3,5-Trisubstituted-2-pyrazolines Derivative for Analgesic Potential: Design, Synthesis, and Characterization of New 1,3,5-Trisubstituted-2-pyrazolines Derivative for Analgesic Potential - Tiwari, O. P. (International Journal of Pharmaceutical & Biological Archive, 2020)
Objective: The objective of the paper was to design, synthesis, and characterization of new 1,3,5-trisubstituted-2-pyrazolines derivative and to evaluate for analgesic potential. Materials and Methods: The 1,3,5-tri-substituted-2-pyrazolines derivatives have been synthesized by the reaction of chalcone derivatives with 4-hydrazinylbenzene sulfonamide hydrochloride and phenyl hydrazine hydrochloride. Total 16 compounds have been synthesized and characterized by the IR, 1HNMR, and mass spectral analysis. Proposed compounds have been evaluated for analgesic activity. The synthesized compounds also evaluated for the analgesic activity by the following two methods, that is, hot plate test method and acetic acid induced writhing in mice. Pentazocine and acetyl acetic acid were used as standard drug for compare the efficacy. Results and Discussion: The analgesic activity of the 16 synthesized compound series A1-A8, and B1-B8 has been evaluated using hot plate test method and acetic acid induced writhing in mice. The results of the evaluation have been viewed by taking pentazocine and acetyl acetic acid as the standard drug. In hot plate test, series A1-A8, shown delay the paw withdrawal latency time for compound A2 (10.30 s), A4 (9.45 s), A7 (11.65 s), and A8 (11.26 s) after 90 min. In series, B1-B8 shown delay the paw withdrawal latency time for compound B2 (9.10 s) and B7 (10.42 s) after 90 min, inhibit the pain sensation, and inhibit pain produced by thermal means. Synthesized compounds of series A1-A8, compounds A2, A5, A6, A7, and A8 were shown 83.00, 76.01, 80.34, 86.99, and 88.15 were shown percent inhibition, significantly (p<0.05 and p<0.001, respectively) and reduced the number of wriths induced by 0.6% acetic acid at the dose of 10 mg/kg. Acetylsalicylic acid (10 mg/kg) appears to be better effective in reducing the number of wriths, it significantly (P < 0.001) reduced the number of wriths by 99.0%. The compounds B1, B3, and B4 have shown least active activity. These all finding suggest that these synthesized compounds have the potential as analgesic agent. Conclusion: The 1,3,5-pyrazoline derivatives has been successfully synthesized and evaluated for analgesic activity of mice model and results data indicate that compounds A2, A5, A6, A7, and A8 were shown 83.00, 76.01, 80.34, 86.99, and 88.15%, and compounds B2, B7, and B8 were shown 72.25, 74.27, and 74.56% inhibitions. The presence of SO2NH2 is essential for analgesic activity.